Penerapan Model Cooperative Integrated Reading And Composition (CIRC) Terhadap Kemampuan Menulis Teks Negosiasi Siswa Kelas X SMA Al Washliyah Pasar Senen - Revika Ananda Putri; Trisnawati Hutagalung (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to describe the results of implementing the Cooperative Integrated Reading and Composition (CIRC) model on students' ability to write negotiating texts. The method used in this research is an experiment with one group pretest-posttest. The sample of this study was students of class X Science and Social Sciences at SMA Al Washliyah Pasar Senen. The data in this study were obtained through documentation, interviews and tests. Based on the results of this study, the results showed that the ability of students in writing negotiating texts that received the application of the Cooperative Integrated Reading and Composition (CIRC) model increased. The results of the pre-test showed that the average student score was 63, as many as 37.5% or nine students who completed and 62.5% or 15 students who did not complete. While the results of the post test showed that the average student score was 79, as many as 95.83% or 23 students and 4.17% or 1 student who did not complete. So, there is an increase in the ability to write negotiating texts for class X SMA Al Washliyah Pasar Senen by applying the Cooperative Integrated Reading and Composition (CIRC) model.